2000
DOI: 10.1038/sj.leu.2401649
|View full text |Cite
|
Sign up to set email alerts
|

2-Chloro-2′-deoxyadenosine induces apoptosis through the Fas/Fas ligand pathway in human leukemia cell line MOLT-4

Abstract: The mechanism of apoptosis induced by 2-chloro-2Ј-deoxyadenosine (2CdA) in human leukemia cell line MOLT-4 was investigated. 2CdA induced increases of 3Ј-OH ends of genomic DNA, ladder-like DNA fragmentation and phosphatidylserine translocation to the outer membrane, which are apoptotic characteristics. These apoptotic phenomena induced by 2CdA were inhibited by cycloheximide (CHX; a protein synthesis inhibitor), deoxycytidine (dC; a substrate of deoxycytidine kinase), acetyl Ile-Glu-Thr-Asp aldehyde (Ac-IETD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 41 publications
5
50
0
Order By: Relevance
“…41 The inhibition by CdA of the actively ongoing basal DNA repair may result in the accumulation of unrepaired lesions and explain why this drug elicits, in certain conditions, a typical DNA damage response. [42][43][44] The clinical relevance of our findings is suggested by the fact that sizable inhibition Leukemia of DNA repair is already seen at 0.05 m CdA ( Figure 5), a concentration achieved in vivo after bolus infusion of CdA.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…41 The inhibition by CdA of the actively ongoing basal DNA repair may result in the accumulation of unrepaired lesions and explain why this drug elicits, in certain conditions, a typical DNA damage response. [42][43][44] The clinical relevance of our findings is suggested by the fact that sizable inhibition Leukemia of DNA repair is already seen at 0.05 m CdA ( Figure 5), a concentration achieved in vivo after bolus infusion of CdA.…”
supporting
confidence: 54%
“…Indeed, the respective effects of CdA and UV could combine to synergistically initiate the two major apoptosis pathways, the Apaf-1-and the Fas/Fas-L-mediated pathways, that both converge with the irreversible activation of caspase-3. [42][43][44]50 Favorable interactions have been shown between various nucleoside analogs and DNA-damaging agents, leading to clinical trials. 6,19,51,52 In conclusion, we demonstrate for the first time that CdA inhibits the resynthesis step of DNA repair in B-CLL cells, and that this may be the basis (entirely or partially) for the synergism between CdA and UV light or alkylating agents.…”
mentioning
confidence: 99%
“…Previous reports suggested an involvement of death receptor signaling and caspase-8 (Nomura et al, 2000) or a direct activation of the mitochondria or the APAF-1/apoptosome complex in nucleoside analogue-induced apoptosis (Genini et al, 2000a, b). To functionally dissect the mechanism of apoptosis induced by the nucleoside analogues cladribine and fludarabine, we employed Jurkat T cells lacking caspase-8, FADD or overexpressing either Bcl-2 or a dominant-negative mutant of caspase-9.…”
Section: Resultsmentioning
confidence: 99%
“…Previous data have suggested that cytotoxic drugs induce cell death by activation of the CD95/Fas pathway, for instance in doxorubicin-induced apoptosis of leukemic T cells (Fulda et al, 2000) and in cladribineinduced cell death (Nomura et al, 2000). Other groups, however, could not confirm these findings and established a CD95/Fas and caspase-8-independent mechanism upon activation of a nuclear stress program by genotoxic agents (Eischen et al, 1997;Engels et al, 2000;Newton and Strasser, 2000;Wieder et al, 2001;von Haefen et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…93,151,152 Thus, drug-induced apoptosis definitively does not depend on CD95/Fas or other death receptors. The caspase-8 activation observed in various systems of anticancer therapy-induced cell death 93,149,[152][153][154] therefore represents a downstream signaling event which may, nevertheless, be involved in the amplification of apoptosis execution.…”
Section: Death Receptors In Radio-and Chemotherapymentioning
confidence: 99%